Distance Education in Religion and Catechesis during an Year of Pandemy - Spirova, Polina (Forum Theologicum Sardicense, 2025)
Polina Spirova, Distance Education in Religion and Catechesis during an Year of Pandemy. The article presents the results of research into the methods of conducting online education for the subject of Religion in middle schools and Sunday schools from March 2020 to March 2021. It outlines the main challenges teachers faced, the solutions they developed, the sources of their support, and students' attitudes towards online Religion education. The study identifies problematic areas that require increased support for teachers from governmental and Christian institutions, as well as non-governmental organizations. Additionally, it describes the opportunities that distance learning offers in the field of Religious education.